Factors supporting teamwork communication in clinical pathways: systematic literature review - Mater, Wasef (Asian Research Publishing Network, 2015)
This systematic review presents the factors that influence teamwork communication, when using clinical pathways, and the relationships between these factors. These factors will support and promote teamwork communication when using clinical pathways. Extensive research was conducted on four databases, including Medline, Scopus, science direct, and Google scholar. From this search, we identified three dimensions of factors that influence teamwork communication, namely (teamwork, tasks and context) and every dimension has its own factors. A set of indicators and factors influence teamwork communication, and these factors are classified into three dimensions based on the systems theory, namely input, process and output. The factors that are investigated in this study have a positive influence on teamwork communication, and these factors will be used as guidelines for developing a framework for implementing clinical pathways that support teamwork communication in the healthcare domain